Elite Cohesion and Its Historical Sources: Analyzing its Impact on Democratization in Nigeria and Botswana - Aboutera, Aliaa Magdy (AUC Knowledge Fountain, 2025)
This thesis examines the divergent democratization trajectories of Botswana and Nigeria, focusing on the role of colonial legacies and post-colonial elites in shaping elite cohesion. While both countries experienced British colonial rule, their transitions to democracy in the post-independence period have differed significantly. This study argues that elite cohesion, although insufficient on its own, is a critical facilitating factor in democratic consolidation that warrants greater attention in the democratization literature. This cohesion is largely shaped by the sociology of political elites, with historical contexts influencing how elites organize. Through process tracing, the thesis argues that colonialism in Botswana did not fragment elites to the extent seen in Nigeria, where British divide-and-rule strategies fostered deep ethnic, regional, and religious cleavages. In contrast, Botswana’s relatively homogenous elite structure and limited colonial interference allowed for a smoother transition to democracy. In that sense, the thesis attempted to integrate elite cohesion as well as sociology of political elites into already existing models of democratization.